Subiekt semantyczny w rosyjskich zdaniach typu можно+infinitivus w porównaniu z językiem polskim - Rudyk, Anna (Przegląd Rusycystyczny, 2012)
Anna Rudyk Uniwersytet Rzeszowski, Rzeszów, Poland annarudyk@wp.pl СЕМАНТИЧЕСКИЙ СУБЪЕКТ В РУССКИХ ПРЕДЛОЖЕНИЯХ ТИПА МОЖНО+INFINITIVUS ПО СРАВНЕНИЮ С ПОЛЬСКИМ ЯЗЫКОМ Резюме целью настоящей статьи является сравнение способов выражения семантического субъекта в русских предложениях типа можно + infinitivus и в их польских эквивален-тах. Семантический субъект — это производитель действия или носитель состояния, названного предикатом. В анализируемых предложениях семантический субъект может быть назван формой косвенного падежа, чаще всего — дательного. Семантический субъект может также восстанавливаться из контекста или быть устраненным. так как анализируемым предложениям часто соответствуют польские предложения с личной формой глагола, выразителем субъекта в польском переводе может быть личное окон-чание глагола или сушествительное (местомение) в именительном падеже. SEMANTIC SUBJECT IN THE RUSSIAN SENTENCES OF THE TYPE МОЖНО+INFINITIVuS COMPARED WITH POLISH ONES Summary The central claim of this article is the comparison of the ways of expressing of the se-mantic subject in the Russian sentences of the type можно + infinitivus and in their Polish equivalents. The semantic subject is an element of the predicative-argumentative structure. It denotes a performer of an action or a bearer of a feature that is expressed by the predicate. In the analyzed sentences the semantic subject can be conveyed explicitly in the form of an oblique case, most often — the dative case. It can also appear from the context or remain unnamed. Because the Polish sentences with the personal form of the verb are frequent equivalents of the analyzed units, the personal flexion of the verb or a noun or a pronoun in nominative case can express the semantic subject in Polish translations well.